Entre os sonhos possíveis e as vivências reais: projetos de vida de participantes de um Grupo de Mulheres em um Centro de Convivência na cidade de São Carlos - SP - Santos, Ana Lívia Pedroso dos (Universidade Federal de São Carlos, 2025)
Introduction: The term "life project" has been widely discussed, especially in the context of education and youth, as it is a notion closely tied to this stage of life and has recently been broadly incorporated as a curricular component in basic education in various Brazilian states. However, understanding that the construction of life projects extends throughout an individual's life journey, this study focuses on the life projects of adult women, considering the intersections of gender and social vulnerability. When exploring the possibilities of creating, sustaining, and realizing life projects within the context of the structural disparities experienced by women in the country, questions arise regarding the feasibility of these projects in lives potentially marked by violence. Objective: To understand the perception of women participating in the Women's Group at the complementary unit of the Social Assistance Reference Center (CRAS) in Cidade Aracy, São Carlos (SP), regarding what life projects are and how they relate them to gender experiences, the lived experience of being a woman, as well as their connection to social protection/risk. Methodological Approach: This study is aligned with action research, which can be conceived as a method or strategy of social research aimed at understanding a phenomenon and its characteristics to support the formulation of appropriate social, educational, technical, and/or political responses. To gather information, four directed meetings were held with a Women's Group located in the Jardim Zavaglia neighborhood in São Carlos, SP. Based on the theoretical-methodological principles of social occupational therapy, Activity, Dynamics, and Project Workshops were conducted, with records made through audio recordings, photographs, and field diaries. The collected data were compiled and analyzed to create explanatory syntheses that could enhance the understanding of the relationships between life projects and the experiences of the women participating in the study. Results: The research revealed the relationship between the experience of being a woman and the challenges in realizing life projects. Factors such as the overload of domestic responsibilities and caregiving—especially for children—and the fragility of social support networks significantly limit their personal and professional development opportunities. On the other hand, the formation of a Women's Group proved to be a powerful tool for mutual support and the encouragement of both personal and collective projects. Final Considerations: The findings of this research reinforce the importance of creating spaces that support women's development, promoting the strengthening of social bonds and autonomy, with the goal of reducing the social disparities they face. These initiatives aim to foster emancipatory processes that expand the possibilities for realizing life projects and dreams.
Between possible dreams and real experiences: life projects of participants in a Women's Group at a Community Center in the City of São Carlos - SP
Keywords: Mulheres; Estudos de Gênero; Terapia Ocupacional; Projetos de Vida; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 5. Igualdade de Gênero